Antioxidant activity, phenolic compound content and phytochemical constituents of eclipta prostrate (linn.) linn - Pukumpuang,W. (Chiang Mai University, 2015)
This study was carried out to investigate antioxidant activity, total phenolic content and phytochemical constituents of crude extract and fractions of Eclipta prostrata. Aqueous, ethanolic and various fractions of E. prostrata extracts were elucidated for antioxidant activity using DPPH assay and determined total phenolic content by Folin-Ciocalteau method. Moreover, the ability of plant extract on protein oxidation protection was also analysed. The results indicated that the EP07 fraction had the highest DPPH radical scavenging activity and total phenolic contents with GAE values 142.918 ± 0.762 and 493.205 ± 10.174 mg GAE/g extract, respectively. Moreover, crude ethanolic extract of E. prostrata could inhibit protein degradation induced by H2O2/Cu2+ catalyzed reaction by 51.94, 57.91, 62.69 and 63.23 %, after treatment with the crude extract at concentrations of 5, 10, 15 and 20 mg/ ml, respectively. In addition, flavonoids were found as major constituents in the EP07 fraction. Therefore, extracts of E. prostrata should be used as antioxidant and dietary supplement.